Level of competencies in Comprehensive Health Care in medical students through the Mini-Clinical Evaluation Exercise (MINI-CEX) - Contreras, Pavel J. (2025)
Objective: To assess the level of competencies in Comprehensive Health Care in medical students before and after Family Medicine rotation through the Mini-Clinical Evaluation Exercise (MINI-CEX). Methods: A quantitative, quasi-experimental, pre-post study was conducted at primary care teaching facilities on 115 senior medical students. The Mini-CEX instrument was applied at the beginning and at the end of a month of a family medicine rotation. The evaluation was carried out by teachers trained in the use of Mini-CEX. The study collected the results and analyzed them with the statistical package STATA 17.0. Results: The average age was 23.4 ± 1.4 years, and 61.7% were women. At the beginning of the rotation, 15% of the students had a satisfactory global evaluation, while at the end of the rotation, 88% had a satisfactory evaluation. Clinical judgment was the competence which increased the most (68%). Cronbach's Alpha resulted in 0.9383. Conclusions: The training of medical students in a family medicine rotation contributes to the achievement of competencies in a comprehensive approach.